Incident type 2 diabetes mellitus after initiation of common HIV antiretroviral drugs. (1st January 2021) - Hsu, Ricky; Brunet, Laurence; Fusco, Jennifer S.; Mounzer, Karam; Vannappagari, Vani; Henegar, Cassidy E.; Van Wyk, Jean; Curtis, Lloyd; Lo, Janet; Fusco, Gregory P.
Abstract : Objectives: To describe the prevalence and incidence of prediabetes and type 2 diabetes mellitus (T2DM) among people living with HIV (PLHIV) and evaluate the association between antiretroviral therapy (ART) initiation with dolutegravir (DTG), elvitegravir/cobicistat (EVG/c), raltegravir (RAL), or boosted darunavir (bDRV) and incident T2DM. Design: Longitudinal study based on electronic health records of 29 674 PLHIV from the Observational Pharmaco-Epidemiology Research and Analysis (OPERA) cohort. Methods: Calculate prevalence of prediabetes and T2DM at regimen initiation. Among PLHIV without prevalent disease, estimate prediabetes and T2DM incidence (Poisson regression) and association between regimen and incident T2DM (multivariate Cox proportional hazards regression). Analyses stratified by ART experience. Results: Among ART-naive and ART-experienced/suppressed PLHIV, the estimated prevalence of prediabetes was 8 and 11%; that of T2DM was 4 and 10%, respectively. The T2DM incidence rate was 9 per 1000 person-years [95% confidence interval (CI): 8–11] among ART-naive and 13 per 1000 person-years (95% CI: 12–15) among ART-experienced/suppressed PLHIV, with no statistically significant differences between regimens. Compared with DTG, no statistically significant association between T2DM risk and regimen was observed among ART-naive on EVG/c [adjusted hazard ratios: 0.70 (95% CI: 0.47–1.05)] or bDRV [0.53 (0.26–1.04)] and ART-experienced/suppressed on EVG/c [0.96 (0.70–1.33)], RAL [1.17 (0.70–1.96)] or bDRV [0.90 (0.57–1.42)]. Conclusion: No increased risk of T2DM was observed with EVG/c, RAL or bDRV compared with DTG in ART-naive and experienced PLHIV. However, despite a large cohort, there was a small number of events and differential risk cannot be excluded. Abstract : Supplemental Digital Content is available in the text